The B-cell specific transcription factor, Oct-2, promotes Epstein-Barr virus latency by inhibiting the viral immediate-early protein, BZLF1. - Amanda R Robinson; Swee Sen Kwek; Shannon C Kenney (PLoS Pathogens, 2012)
The Epstein-Barr virus (EBV) latent-lytic switch is mediated by the BZLF1 immediate-early protein. EBV is normally latent in memory B cells, but cellular factors which promote viral latency specifically in B cells have not been identified. In this report, we demonstrate that the B-cell specific transcription factor, Oct-2, inhibits the function of the viral immediate-early protein, BZLF1, and prevents lytic viral reactivation. Co-transfected Oct-2 reduces the ability of BZLF1 to activate lytic gene expression in two different latently infected nasopharyngeal carcinoma cell lines. Furthermore, Oct-2 inhibits BZLF1 activation of lytic EBV promoters in reporter gene assays, and attenuates BZLF1 binding to lytic viral promoters in vivo. Oct-2 interacts directly with BZLF1, and this interaction requires the DNA-binding/dimerization domain of BZLF1 and the POU domain of Oct-2. An Oct-2 mutant (Δ262-302) deficient for interaction with BZLF1 is unable to inhibit BZLF1-mediated lytic reactivation. However, an Oct-2 mutant defective for DNA-binding (Q221A) retains the ability to inhibit BZLF1 transcriptional effects and DNA-binding. Importantly, shRNA-mediated knockdown of endogenous Oct-2 expression in several EBV-positive Burkitt lymphoma and lymphoblastoid cell lines increases the level of lytic EBV gene expression, while decreasing EBNA1 expression. Moreover, treatments which induce EBV lytic reactivation, such as anti-IgG cross-linking and chemical inducers, also decrease the level of Oct-2 protein expression at the transcriptional level. We conclude that Oct-2 potentiates establishment of EBV latency in B cells.